Fluid Migration in a Subducting Viscoelastic Slab. (3rd February 2018) - Morishige, M.; van Keken, P. E.
Abstract: Metamorphic dehydration reactions in a subducting slab release fluids that trigger arc volcanism and are thought to be responsible for intermediate‐depth seismicity. The fluid flow from the source is controlled by buoyancy and compaction pressure which is modified by viscous and elastic effects. In this paper, we investigate how fluid migrates in viscoelastic slab by using 2‐D and 3‐D numerical models based on a theory of two‐phase flow. When bulk viscosity is sufficiently low, viscosity plays a dominant role and fluid goes up almost vertically soon after its release producing porosity waves. When a higher bulk viscosity is assumed, a large amount of fluid is trapped in a high porosity region produced by the fluid source and migrates along the source except for a case where the ratio of permeability ( K ) to fluid viscosity ( μ ) is relatively low. We also find that porosity increases in the deeper part of the fluid source in cases with intermediate and low values of K / μ . In 3‐D, fluid focusing occurs where the slab bends away from the trench causing a local increase in porosity and compaction pressure. These findings may help us explain several types of observations in subduction zones including slow earthquakes at the plate interface, low seismic wave velocities in the oceanic crust, double seismic zones in the slab, and shallow subduction angle at the bend of the slab. Key Points: We investigate fluid behavior in a subducting viscoelastic slab using 2‐D and 3‐D numerical models based on a theory of two‐phase flow Porosity increases in the deeper part of the fluid source when the ratio of permeability to fluid viscosity is relatively low 3‐D fluid focusing occurs where the slab bends away from the trench, leading to the increase in porosity and compaction pressure at the bend